Improving Science Learning Outcomes in Elementary School trough a Problem-Based Learning Model Assisted by Word Wall - Pipit Hima Puspita; Deni Setiawan (Universitas Pendidikan Ganesha, 2025)
The use of less innovative learning models and media can negatively affect student learning outcomes due to decreased involvement and motivation in the learning process. This study aims to analyze the effectiveness of applying the Problem-Based Learning (PBL) model, supported by Word Wall media, in improving science learning outcomes for grade IV students at elementary school. This study uses an experimental method with a quasi-experimental design, specifically a non-equivalent control group design. Data collection was carried out through tests (pretest and posttest), observations, interviews, and documentation. Normality and homogeneity tests were conducted on the initial data, while final data analysis employed t-tests and N-Gain. The t-test results showed a significance value of 0.00 (sig. <0.05), indicating that H₀ was rejected and Hₐ was accepted. The N-Gain analysis revealed that the experimental group obtained an average score of 58.33% (medium category), while the control group scored only 25.08% (low category). These findings suggest that the application of the PBL model, supported by Word Wall media, is effective in improving science learning outcomes for grade IV students at a public elementary school.